Influencing Factors Analysis on Land-Lost Farmers’ Happiness Based on the Rough DEMATEL Method - Lixia Liu; Tingting Wang; Lei Xie; Xueli Zhan (Discrete Dynamics in Nature and Society)
In this paper, fifteen indicators from four dimensions are selected to construct an evaluation system for the happiness of land-lost farmers. The factors affecting the happiness of land-lost farmers are analyzed using the rough DEMATEL method. The results show that land expropriation compensation (F6) and job stability (F7) are the driving factors for improving the happiness of land-lost farmers. The government can improve the social environment policies, such as land acquisition, social security, and employment to influence other factors and improve the level of happiness of land-losing farmers. This study has important guiding significance and reference value for the reform of China’s land expropriation, the protection of land-lost farmers’ rights and interests and the improvement of their happiness, and the maintenance of social harmony and stability.